OPTIMIZATION OF CELLULASE PRODUCTION FROM MARINE BACTERIUM BACILLUS CEREUS C9 BY SUBMERGED FERMENTATION - -, Yopi -; Rahmani, Nanik (Teknologi Indonesia, 2016)
Cellulase is one of industrial important enzymes in conversion of lignocellulosic biomass into valuable products such as bioethanol produced by fermentation. Successful bioconversion of cellulosic biomass mainly depends on the nature of cellulose sources of cellulolytic enzyme and optimal conditions for production of enzymes. An extracellular cellulase production by marine bacterium Bacillus cereus C9 was optimized by using submerged fermentation (SMF) on commercial substrate (CMC). The fermentation condition such as substrate concentration, pH medium, temperature fermentation, and carbon source were optimized. The optimum condition found for cellulase production were substrate concentration 2.0% (b/v), pH medium 5, temperature fermentation 30C, and glucose as a carbon source with activity 4.42 U ml-1on 96 hours of fermentation.